1996
DOI: 10.1097/00000539-199607000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent Outcomes During Postoperative Patient-Controlled Intravenous Analgesia with Lidocaine Plus Morphine Versus Morphine Alone

Abstract: To evaluate a possible opioid-sparing effect of intravenous lidocaine we conducted a randomized, double-blind clinical trial. Patients undergoing intraabdominal surgery under general anesthesia were treated with patient-controlled analgesia (PCA) in three groups: Group 1 (n = 100; morphine 1 mg/mL), Group 2 (n = 44; morphine 1 mg/mL plus lidocaine 10 mg/mL), and Group 3 (n = 51; morphine 1 mg/mL plus lidocaine 20 mg/mL). Pain was evaluated using a 0-10 visual analog scale in the postanesthesia care unit (PACU)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 19 publications
1
6
1
Order By: Relevance
“…Contrary to our finding, however, other studies failed to demonstrate a significant analgesic effect of lidocaine in the post‐operative period 23,24 . The discrepancy might be related to the types of surgery or the timing of lidocaine administration.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our finding, however, other studies failed to demonstrate a significant analgesic effect of lidocaine in the post‐operative period 23,24 . The discrepancy might be related to the types of surgery or the timing of lidocaine administration.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of Moslemi et al on patients undergoing gynecologic laparoscopic surgery indicate that infusion of lidocaine (1.5 mg/kg) could significantly affect postoperative pain reduction [18]. Also, it has been shown that adding lidocaine to morphine PCA, compared to morphine PCA alone, has no significant efficacy in postoperative pain reduction after abdominal surgery [19]. The results of these studies are consistent with our study.…”
Section: Discussionsupporting
confidence: 90%
“…16 Various lidocaine infusion protocols have been used only during surgery, 4,12,17,18 intraoperatively and for 24 h postoperatively, 11,13,19 -21 or exclusively after surgery with patient-controlled analgesia. 22 Only two trials using patient-controlled analgesia associating morphine plus lidocaine 21 and perioperative 22 lidocaine administration failed to demonstrate opioid-sparing effect. The other studies reported various impacts on analgesia associated with a reduction of postoperative morphine requirement but opioid consumption was generally only secondary endpoints (except in three studies).…”
Section: Discussionmentioning
confidence: 99%